Perspektif Iman Kristen Terhadap Perilaku Berpakaian Remaja Citayam Di Fashion Week Dukuh Atas - Napitu, Hernita; Hermanto, Yanto Paulus (LOGIA: Jurnal Teologi Pentakosta, 2022)
The desire for existence is a behavior that is often done by teenagers, this study explores how to dress teenagers at Citayam fashion week in Dukuh Atas according to the fashion trends that are currently trending. The behavior of Citayam teenagers in “fashion week” activities in Dukuh Atas caused a lot of negative views from the community, government and religious leaders. Inappropriate behavior of teenagers in dressing, everywhere men wear women's clothes while swaying, littering, gatherings for too long and other problems. This study uses a literature study approach to find the main picture of the intended research where the results of the study show that teenagers in Dukuh Atas fashion week need proper education from their parents, school, environment and church. The most important role comes from parents as role models. Education in the family will shape the identity of adolescents. These teenagers will be different from other teenagers when they know their identity so that they are seen as good by societyKeyword: Citayam Fashion, Teen Fashion Behavior, Teen Identity Keinginan untuk eksistensi adalah perilaku yang sering di lakukan oleh remaja, penelitian ini menelusuri cara berpakaian fashion week remaja Citayam di Dukuh Atas sesuai mode fashion yang sedang trend belakangan ini. Perilaku remaja Citayam dalam kegiatan “fashion week” di Dukuh Atas menimbulkan banyak pandangan negatif dari masyarakat, pemerintah dan tokoh agama. Perilaku remaja yang kurang pantas dalam berpakaian, dimana-mana laki-laki menggunakan pakaian perempuan sambil berlenggak lenggok, membuang sampah sembarangan, kumpul-kumpul terlalu lama dan masalah lainnya. Penelitian ini menggunakan pendekatan studi pustaka untuk menemukan gambaran pokok penelitian yang di maksud dimana hasil penelitian menunjukkan remaja-remaja di fashion week Dukuh Atas memerlukan pendidikan yang tepat dari orangtua, sekolah, lingkungan dan gereja. Peranan paling penting berasal dari orangtua sebagai teladan. Pendidikan dalam keluarga akan membentuk jati diri remaja. Remaja-remaja itu akan berbeda dengan remaja lainnya ketika mereka mengetahui jati dirinya sehingga dipandang baik oleh masyarakat. Kata Kunci: Fashion Citayam, Perilaku Fashion Remaja, Jati diri Remaja